Chemical characterisation of pasture‐ and grain‐fed beef related to meat quality and flavour attributes. (16th October 2012) - Tansawat, Rossarin; Maughan, Curtis A. J.; Ward, Robert E.; Martini, Silvana; Cornforth, Daren P.
Summary This study examined pasture (PF) and grain feeding (GF) effects on meat quality and nutritional attributes, and correlated sensory attributes with cooked meat volatiles. GF rib steaks had higher fat content (P < 0.05), and were lighter, redder and more yellow (P < 0.05). PF beef contained more (P < 0.05) omega‐3 fatty acids, despite having lower fat content. PF beef had higher antioxidant capacity, and lower oxidation indices (P < 0.05). Diets influenced the volatile profile of cooked meat. Flavour descriptors barny, gamey and grassy were associated with PF, and were uniquely shown here to be positively correlated with aroma volatiles benzaldehyde, toluene, dimethyl sulfone, 3‐heptanone, 2‐ethyl‐1‐hexanol and hexadecanoic acid methyl ester (P < 0.05). GF beef had higher (P < 0.05) levels of hexanal, 1‐octen‐3‐ol, 2, 3‐octandione, and 2, 6‐bis(1, 1‐dimethylethyl)‐4‐ethyl‐phenol, uniquely associated with umami and juicy flavours. The main positive nutritional attribute of PF beef was its low fat content.